Capsaicin: beyond TRPV1 - Juárez-Contreras, Rebeca; Mota-Carrillo, Edgardo; Piedra-Ramírez, Angelica; Farías-Sánchez, Daniel; González-Ramírez, Ricardo; Morales-Lázaro, Sara Luz (Frontiers in Nutrition, 2025)
Capsaicin, the chili-pungent compound, has a peculiar chemical structure that allows it to impact mammalian physiology. Besides its classical effects through activating the Transient Receptor Potential Vanilloid type 1 (TRPV1), growing experimental evidence demonstrates that capsaicin has pleiotropic actions in a TRPV1-independent manner. These effects are achieved by modifying the membrane features or interacting with unclassical putative molecular targets. Here, we will summarize the representative information related to the capsaicin actions through unclassical and TRPV1-independent molecular mechanisms, and we will discuss the impact of these effects on non-neuronal cells and mammalian physiology.